2019
DOI: 10.1002/ange.201900600
|View full text |Cite
|
Sign up to set email alerts
|

Carbene‐Catalyzed Enantioselective Decarboxylative Annulations to Access Dihydrobenzoxazinones and Quinolones

Abstract: Ad irect decarboxylative strategy for the generation of aza-o-quinone methides (aza-o-QMs) by N-heterocyclic carbene (NHC) catalysis has been discovered and explored. This process requires no stoichiometric additives in contrast with current approaches.A za-o-QMs react with trifluoromethyl ketones through af ormal [4+ +2] manifold to access highly enantioenriched dihydrobenzoxazin-4-one products, which can be converted to dihydroquinolones through an interesting stereoretentive aza-Petasis-Ferrier rearrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 79 publications
1
3
0
1
Order By: Relevance
“…1 H NMR (400 MHz, DMSO- d 6 ): δ 7.90 (d, J = 8.3 Hz, 1H), 7.71 (d, J = 1.7 Hz, 1H), 7.52 (dd, J = 8.3, 1.5 Hz, 1H), 3.46 (s, 3H). Characterization matched the previous report …”
Section: Methodssupporting
confidence: 89%
“…1 H NMR (400 MHz, DMSO- d 6 ): δ 7.90 (d, J = 8.3 Hz, 1H), 7.71 (d, J = 1.7 Hz, 1H), 7.52 (dd, J = 8.3, 1.5 Hz, 1H), 3.46 (s, 3H). Characterization matched the previous report …”
Section: Methodssupporting
confidence: 89%
“…For example, Scheidt and co-workers disclosed an NHC-mediated [4 + 2] cycloaddition of isatoic anhydride and trifluoromethyl ketones. Various enantioenriched dihydrobenzoxazin-4-ones functionalized with a CF 3 group can be produced with this protocol (Scheme 13a) [63]. In this transformation, the generation of an NHC-bonded intermediate is vital for the success of the reactions.…”
Section: Discussionmentioning
confidence: 99%
“… [7] In 2019, Scheidt and co‐workers disclosed that carbene could activate N ‐methylisatoic anhydrides for enantioselective N ‐nucleophilic addition reaction via aza ‐ o ‐quinone methides ( aza ‐ o ‐QMs) (Figure 1 a). [8a] In the same year we found that addition of a carbene catalyst to indole aldehydes at a remote site could enable an asymmetric NH functionalization [8b] . Very recently, independent studies reported by Biju, [9a] Hui [9b] and us [9c] showed that under the catalysis of NHCs the N ‐centered nucleophiles could be functionalized via the formation of aza ‐fulvene intermediates (Figure 1 a).…”
Section: Introductionmentioning
confidence: 84%